2020
DOI: 10.1021/acs.jced.9b01018
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Pressure Dependence of the Viscosity of the Ionic Liquid 1-Butyl-3-methylimidazolium Acetate

Abstract: Viscosities obtained with a falling-body viscometer are reported at pressures up to 300 MPa, over the temperature range 278–353 K, for 1-butyl-3-methylimidazolium acetate ([BMIM]­[Ac]) samples dried under high vacuum with water content [106 × w(H2O) = 258 and 1180] and ion purity x > 0.992. Atmospheric pressure densities are reported for 273–363 K. Comparison is made with literature viscosities and densities at 0.1 MPa. There is a very large variation in the former, which seems in part due to differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…¶ As in ref. 4 and our other work, 15,16,37 the logarithms of the Rosenfeld reduced quantities were fitted to polynomials in 1/(TV) g for selected values of g with polynomial orders from 2 to 3, depending on the range of available data, with the order being kept as low as needed to give sensible fits commensurate with the experimental precision; g is chosen by iteration to minimize the standard deviation of the fit. Fig.…”
Section: Thermodynamic Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…¶ As in ref. 4 and our other work, 15,16,37 the logarithms of the Rosenfeld reduced quantities were fitted to polynomials in 1/(TV) g for selected values of g with polynomial orders from 2 to 3, depending on the range of available data, with the order being kept as low as needed to give sensible fits commensurate with the experimental precision; g is chosen by iteration to minimize the standard deviation of the fit. Fig.…”
Section: Thermodynamic Scalingmentioning
confidence: 99%
“…In previous studies we have reported on the pressure and temperature dependence of ion self-diffusion coefficients, [1][2][3][4][5][6][7] the electrical conductivity 1,[8][9][10] and the viscosity 2,6,[11][12][13][14][15][16] of a range of ionic liquids. In statistical mechanical Green-Kubo theory, the self-diffusion coefficients and the conductivity can be written in terms of velocity cross-correlation coefficients (VCC) and it has been found that these show, for a given ionic liquid, very similar viscosity dependence for cation-cation, anion-anion, and cationanion interactions.…”
mentioning
confidence: 99%
“…For example, as shown by Cabeza et al, the conductivity of certain 1-ethyl-3methyl-imidazolium based ionic liquids can increase twentyfold in the range of 258.15 to 298.15 K, and up to a factor of 400 when increasing the temperature to 393.15 K. 18 Molten salts are known to form layers of oppositely charged ions around both cations and anions. These cages play a vital role in the evolution of the viscosity and diffusivity of ILs, [19][20][21] slowing down dynamics and reducing conductivity. 18,22,23 Rattling motions within said cages can be assumed to occur at a fast timescale without significant interaction with neighboring like-charged ions.…”
Section: Introductionmentioning
confidence: 99%
“…32 The viscosities of GuCl : LA and GuCl : LevA are also below that of the common IL [C 4 C 1 im][OAc] (278 mPa s). 33 Hence, these fluids possess improved or comparable viscosities to other, similar non-volatile alternative solvents.…”
mentioning
confidence: 99%